Penerapan Model UTAUT 2 untuk Menjelaskan Minat dan Perilaku Penggunaan Mobile Banking - Nopiani, Ni Kadek Rahayu; Putra, I Made Pande Dwiana (E-Jurnal Akuntansi; Vol 31 No 10 (2021), 2021)
The purpose of this study was to determine the factors that influence the interest and behavior of using mobile banking by applying the UTAUT2 model. The variables used in this study are performance expectations, business expectations, socio-cultural factors, facilitating conditions, hedonic motivation, price values and habits. This research was conducted in Badung Regency. Determination of the sample is done by accidental sampling technique. Data was collected by distributing online questionnaires. The analysis technique used is multiple linear regression. This study shows that interest in using mobile banking is influenced by performance expectations, socio-cultural factors, hedonic motivation and price values. The results of this study also indicate that the behavior of using mobile banking is influenced by conditions that facilitate, habits and interest in use. Keywords: UTAUT2; Interest in using Mobile banking; Mobile banking Usage Behavior.